PERGESERAN KECAKAPAN BERTUTUR DI KALANGAN MAHASISWA BAHASA AKIBAT INTERAKSI BAHASA INDONESIA, BAHASA DAERAH, DAN BAHASA ASING - Yusup Irawan (tuahtalino, 2021)
This study aims to examine the existence of language shifts through shifts in speaking skills due to interactions between Indonesian, regional languages, and foreign languages. The data collection technique used is the recording technique as the main technique, while the interview and direct observation techniques are additional techniques. The respondents of this study were 34 students of the Indonesian language study program and the foreign language study program. Speech data were analyzed with three aspects of oral language skills, namely (2) speech tempo (prosody or intonation), (2) fluency, and (3) lexical (Itkonen, 2010:15-17). The results of the analysis show that there has been a shift in speaking skills from regional languages to Indonesian for all groups of respondents. Even students who are engaged in foreign languages are on average more fluent in foreign languages than in regional languages. These are indicators of a shift in regional languages to Indonesian and a shift in regional languages to foreign languages among this group of students. It can be formulated that the lower the speaking skill of a language is mastered by the speaker, the more vulnerable the language is to be shifted by a language that is more capable of being mastered by the speaker.